Rise of gastro-intestinal nematode egg counts in lactating goats - Costa, Carlos Alberto Fagonde (Pesquisa Agropecuaria Brasileira, 2014)
This experiment evaluated the parturition and lactating influence on the fecal nematode egg counts in female goats. The does were divided into four groups as follows: DND - dry nondewormed does; LND - lactating nondewormed does; DD - dry dewormed does; LD – lactating does, dewormed three to four weeks before parturition. The study was replicated in two parturition seasons. The egg per gram (EPG) counts and the fecal cultures were carried out weekly. In spite of the anthelmintic medication, the does who gave birth in October (middle of the dry season) presented higher EPG counts than the dry does. In the LND group, the EPG rises took place at the third and seventh weeks after parturition. During these peaks, the EPG counts in the LND group were higher (P
Keywords: rise in EPG counts; Haemonchus sp.; epidemiology; goats